Quantifying organic carbon storage and sources in sediments of Dong Rui mangrove forests, Tien Yen district, Quang Ninh province using carbon stable isotope - Nguyen, Pham Thao; Tue*, Nguyen Tai; Quy, Tran Dang; Thai, Nguyen Dinh (Vietnam Journal of Earth Sciences, 2016)
The objective of this study is to quantify the organic carbon (OC) storage and its sources in sediments of Dong Rui mangrove forests, Tien Yen district, Quang Ninh province by analyzing TOC (total organic carbon), TN (total nitrogen), C/N ratios, δ13C isotopes and sediment grain sizes. The results showed that the fine-grained sediment fraction (<63 µm) ranged from 8.58 to 82.10%; TOC, TN contents, C/N ratios and δ13C values ranged from 0.21 to 10.20%, 0.01 to 0.34%, 15.07 to 46.09 and –27.75 to –25.84‰, respectively. The variation of δ13C and C/N ratios, and the correlation between TOC, TN and the fine-grained sediment fractions indicated that mangrove forests play important roles in OC sequestration and accumulation of fine-grained sediments. The OC storage in sediments varied from 16.7 to 78.3 MgC ha-1 with an average of 57.2 ±14.9 MgC ha-1. Nowadays, the mangrove forest area in Dong Rui is about 2194.1 ha, thus, the total OC in sediment pool up to 45 cm in depth, contained 1.26(±0.3)×105 MgC, equivalent to 4.6(±1.2)×105 Mg CO2. These results demonstrated that the conservation of Dong Rui mangrove forest not only provides opportunities for coastal protection and disaster mitigation and other provision values, but also enhancing carbon sequestration and offsetting greenhouse gas emissions.References Alongi, D.M., 2011. Carbon payments for mangrove conservation: ecosystem constraints and uncertainties of sequestration potential. Environmental Science Policy 14, 462-470. Alongi, D.M., Sasekumar, A., Chong, V.C., Pfitzner, J., Trott, L.A., Tirendi, F., Dixon, P., Brunskill, G.J., 2004. Sediment accumulation and organic material flux in a managed mangrove ecosystem: estimates of land - ocean - atmosphere exchange in peninsular Malaysia. Marine Geology 208, 383-402. Bouillon, S., Connolly, R., Lee, S., 2008. Organic matter exchange and cycling in mangrove ecosystems: recent insights from stable isotope studies. Journal of Sea Research 59, 44-58. Bouillon, S., Rao, A.V.V.S., Koedam, N., Dahdouh-Guebas, F., Dehairs, F., 2003. Sources of organic carbon in mangrove sediments: variability. Hydrobiologia 495, 33-39. Christensen, B., 1978. Biomass and primary production of Rhizophoraapiculata Bl. in a mangrove in southern Thailand. Aquat Bot 4, 43-52. Donato, D.C., Kauffman, J.B., Murdiyarso, D., Kurnianto, S., Stidham, M., Kanninen, M., 2011. Mangroves among the most carbon - rich forests in the tropics. Nature Geoscience 4, 293-297. Furukawa, K., Wolanski, E., 1996. Sedimentation in mangrove forests. Mangroves Salt Marshes 1, 3-10. Hedges, J.I., Keil, R.G., 1995. Sedimentary organic matter preservation: an assessement and speculative synthesis. Marine Chemistry 49, 137-139. Kauffman, J.B., Donato, D.C., 2012. Protocols for the measurement, monitoring and reporting of structure, biomass and carbon stocks in mangrove forests, 86 pp., Center for International Forest Research, Bogor, Indonesia. Kristensen, E., Bouillon, S., Dittmar, T., Marchand, C., 2008. Organic carbon dynamics in mangrove ecosystems: A review. Aquat Bot 89, 201-209. Lamb, A., Wilson, G., Leng, M., 2006. A review of coastal palaeoclimate and relative sea-level reconstructions using δ13C and C/N ratios in organic material. Earth Science Reviews 75, 29-57. Lovelock, C.E., Ruess, R.W., Feller, I.C., 2011. CO2 efflux from cleared mangrove peat. PLoS ONE 6, 1-4. Ong, J.E., 1993. Mangroves - a carbon source and sink. Chemosphere 27, 1097-1107. Quy, T.D., Tue, N.T., 2011. Spatial distribution of total organic carbon (TOC), total nitrogen (TN), TOC/TN ratio, and stable carbon isotopes value (δ13C) in surface sediments of Tien Yen Bay, northeast Vietnam. Vietnam Journal of Earth Sciences 33, 615-624 (In Vietnamese). Reimers, C.E., Suess, E., 1983. The partitioning of organic carbon fluxes and sedimentary organic matter decomposition rates in the ocean. Marine Chemistry 13, 141-168. Richard, M., Angus, M., Tim, H., 2011. The potential for mangrove carbon projects in Vietnam. SNV REDD+, Hanoi. Schumacher, B.A., 2002. Methods for the determination of total organic carbon in soils and sediments. U.S. Environmental Protection Agency, Washington. Siikamäki, J., Sanchirico, N., Jardine, J., McLaughlin, S., Morris, D.F., 2012. Blue carbon: global options for reducing emissions from the degradation and development of coastal ecosystems. Resources for future, Washington. Spalding, M., Kainuma, M., Collins, L., 2010. World atlas of mangroves. Earthscan from Routledge, London. Tuan, H.V., Quy, T.D., Vuong, N.V., Nhuan, M.T., 2012. Orientation of functional zoning for sustainable use of environment and natural resources in Tien Yen Bay. Vietnam Journal of Earth Sciences 34, 486-494 (In Vietnamese). Tuan, M.S., Hanh, N.T.H., 2009. Carbon accumulation of Kandeliaobovata (Sheue, Liu & Yong) plantation in the coastal area of Giao Thuy district, Nam Dinh province. Journal of Biology 31, 57-65 (In Vietnamese). Tue, N.T., Dung, L.V., Nhuan, M.T., Omori, K., 2014. Carbon storage of a tropical mangrove forest in Mui Ca Mau National Park, Vietnam. Catena 121, 119-126. Tue, N.T., Hamaoka, H., Sogabe, A., Quy, T.D., Nhuan, M.T., Omori, K., 2011. The application of δ13C and C/N ratios as indicators of organic carbon sources and paleoenvironmental change of the mangrove ecosystem from Ba Lat Estuary, Red River, Vietnam. Environmental Earth Sciences 64, 1475-1486. Tue, N.T., Ngoc., N.T., Quy, T.D., Hamaok, H., Nhuan, M.T., Omori, K., 2012. A cross-system analysis of sedimentary organic carbon in the mangrove ecosystems of Xuan Thuy National Park, Vietnam. Journal of Sea Research 67, 69-76. Van Santen, P., Augustinus, P., Janssen-Stelder, B., Quartel, S., Tri, N., 2007. Sedimentation in an estuarine mangrove system. Journal of Asian Earth Sciences 29, 566-575.